'Sometimes They Are Fun and Sometimes They Are Not': Concept Mapping with English Language Acquisition (ELA) and Gifted/Talented (GT) Elementary Students Learning Science and Sustainability - Katrina Marzetta; Hillary Mason; Bryan Wee (MDPI AG, 2018)
This study presents an 'education for sustainability' curricular model which promotes science learning in an elementary classroom through equity pedagogy. A total of 25 fourth-grade students from an urban, public school in Denver, Colorado participated in this mixed-methods study where concept maps were used as a tool for describing and assessing students' understanding of ecosystem interactions. Concept maps provide a more holistic, systems-based assessment of science learning in a sustainability curriculum. The concept maps were scored and analyzed using SPSS to investigate potential differences in learning gains of English Language Acquisition (ELA) and Gifted/Talented (GT) students. Interviews were conducted after the concept maps were administered, then transcribed and inductively coded to generate themes related to science learning. Interviews also encouraged students to explain their drawings and provided a more accurate interpretation of the concept maps. Findings revealed the difference between pre- and post-concept map scores for ELA and GT learners were not statistically significant. Students also demonstrated an increased knowledge of ecosystem interactions during interviews. Concept maps, as part of an education for sustainability curriculum, can promote equity by providing diverse learners with different-yet equally valid-outlets to express their scientific knowledge.